TRAINING OF COURSERS OF MILITARY UNIVERSITIES IN HAND-TO-HAND COMBAT OF COURSERS (Archive of Conferences, 2020)
This article examines the fact that modern hand-to-hand combat makes great demands on the war - on his combat skills, especially physical and psychological readiness.